Karakteristik Anggota Legislatif dan Kinerja Pemerintah Daerah - zaitul, zaitul; Jefrita, Welly; Rifa, Dandes (Faculty of Economics and Business University of Mataram, 2021)
This study aim to invetigate the relationship between legistlatif’s characteristics and Local Government Performance. Legislative’s characteristic is proxy by size, age, gender and education background of local legislatif ‘s members. Agency theory is used to underpinned this relationship. The secondary data is used and gathered through finance ministry’s website, and general election commissions. Using eighty-one local governments, multivariate regression analyis is applied to analyse the data. classical assumption test is assessed before interpretating the regression result. Based on the t statistic and p-value, all hypohoteses are rejected . however, local government revenue has negative effect on local government performance. Theortically, agency theory could not be used to understand the phonomena. Practical implication discuss in this paper.